Manajemen Strategi Himpunan Mahasiswa Banyuasin (HIMBA) Komisariat UIN Raden Fatah Palembang Dalam Meningkatkan Pengetahuan Keagamaan Anggota - Meta reza; Nurseri Hasna Nasution; Hasril Atieq Pohan (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This thesis is entitled "Strategic Management of the Banyuasin Student Association (HIMBA) UIN Raden Fatah Palembang Commissariat in Increasing Members' Religious Knowledge" This research aims to examine the role of strategic management in increasing the religious knowledge of members of the Banyuasin Student Association. Strategic Management is the right solution to overcome this problem. Strategic Management is a series of decisions that lead to the preparation of long-term strategies using the SWOT analysis technique. This research is qualitative research used in this research is field research. Because data collection is carried out directly at the research location. Meanwhile, the method used is descriptive research. This means that the research only presents the data as it is without intervention or relationship with others, so the data obtained is in the form of interview transcripts, field notes, photos of documents and so on. The data refers to the behavior and responses of respondents. The results obtained from this research indicate that effective strategic management can play an important role in increasing the religious knowledge of members of the Banyuasin Student Association. Several key factors in strategic management that contribute positively are good planning, structured program implementation, and continuous evaluation. Apart from that, collaboration with related parties and the use of information technology also have a positive impact in increasing the effectiveness of strategic management.